(untitled) (Biodiversitas Journal of Biological Diversity, 2016)
Fossil woods in Java Island have been excavated and sold for outdoor ornaments or indoor decoration purposes since 30 years ago. These fossils are in danger of being drained out without known identities, composition and history. This study was aimed to find out the botanical identity and geographical aspect of a newly recovered silicified fossil wood from Banten area in the west region of Java Island. The fossil trunk 28 m in length and 105 cm in diameter was buried in a tuffaceous sandstone layer. The age of the stratum was thought to be Lower Pliocene. A small sample was cut from the outer part of the log and then ground to obtain thin section for anatomical observation. The main anatomical features of the fossil wood are as follows: wood diffuse porous; vessel almost exclusively solitary, vascicentric tracheid present; axial intercellular canal present, distributed in long tangential rows; fibers with distinctly bordered pit. These features show affinities of the fossil wood to the extant wood Dryobalanops of the family Dipterocarpaceae, regardless of the fact that this genus is no longer exists living in the natural forest of the present day Java Island. ïƒ£ 2004 Jurusan Biologi FMIPA UNS Surakarta Keywords: fossil wood, Dipterocarpaceae, Dryobalanoxylon, Pliocene, Java Island